Retail merchandising : consumer goods and services - Samson, Harland E.; Little, Wayne G. (Cincinnati, Ohio : South-Western, 1993)
This book contains 50 projects dealing with job activities in retailing.
Keywords: Management; Retail trade; Consumer; Retail trade